Effects of Fire Duration on the Seismic Retrofitting With Hysteretic Damped Braces of r.c. School Buildings - Mazza, Fabio; Imbrogno, Giovanna (Frontiers in Built Environment, 2019)
School buildings are susceptible to high incidents of fire because of carelessness, faulty electrical installation and arson, raising the attention on their seismic retrofitting after fire exposure. Hot and residual mechanical properties of a reinforced concrete (r.c.) structure exposed to fire depend on duration of the heating and cooling phases. As a consequence, seismic retrofitting of a fire-damaged framed structure may not be effective when the peak temperature during a fire is considered. For a successful retrofit, ultimate capacity resulting from residual properties after cooling needs to be taken into account. To this end, the state secondary school Collina-Castello of Bisignano (Cosenza, Italy), a three-story r.c. framed structure designed in a medium-risk seismic region to comply with a former Italian seismic code, is considered as test structure. Thermal analysis of r.c. frame members is preliminarily carried out for two fire scenarios, on the assumption that the fire compartment is confined to the ground (F0) and first (F1) levels. Moreover, four fire-damage cases are examined, considering only the heating phase, at 30 (i.e., F1) and 45 (i.e., F0) minutes of fire resistance, and the overall fire cycle, for fast, medium and slow phases of cooling. Afterwards, the school is supposed to be retrofitted with hysteretic damped braces (HYDBs), in order to achieve the performance levels imposed by current Italian code in a high-risk seismic zone. Non-linear static and dynamic analyses of the unbraced and damped braced structures are carried out, with reference to the degradation of r.c. frame members for different fire durations in the design procedure of the HYDBs.